Real-World Outcomes With Generic Pomalidomide in Relapsed Refractory Multiple Myeloma—Experience From a Tertiary Care Cancer Center. (2021) - Bondili, Suresh Kumar; Bagal, Bhausaheb; Zawar, Abhinav; Ventrapati, Pradeep; Thorat, Jayashree; Gokarn, Anant; Punatar, Sachin; Nayak, Lingaraj; Bonda, Avinash; Jain, Hashmukh; Sengar, Manju; Khattry, Navin
Abstract : PURPOSE: The prognosis of relapsed and refractory multiple myeloma (RRMM) that is refractory to bortezomib and lenalidomide is very poor wherein the median survival is between 3 and 9 months. We did this retrospective analysis to study the pattern of utilization, tolerance, and outcomes with pomalidomide in these patients having RRMM. MATERIALS AND METHODS: Retrospective analysis of all the patients who were treated with generic pomalidomide at Tata Memorial Centre, Mumbai, during the period of May 2017 to March 2019 was done. Patients with secretory disease and who had completed at least one cycle of pomalidomide were analyzed for response rates, toxicity, and survival outcomes. RESULTS: A total of 81 patients received pomalidomide-based therapy during this study period, out of which 75 were included in the survival analysis. Forty-eight patients (59.3%) were refractory to both lenalidomide and bortezomib. Overall response rate was 58.7%. Five patients (6.7%) achieved complete response, very good partial response was seen in 13 patients (17.3%), and partial response was seen in 26 patients (34.7%). After a median follow-up of 11 months (range 2-27 months), median progression-free survival was 9.1 months (95% CI, 5.4 to 12.9 months). Median progression-free survival for patients who were refractory to both lenalidomide and bortezomib versus nonrefractory was 5.5 and 12.6 months, respectively, which was significant statistically ( P = .04, hazard ratio, 0.35, 95% CI, 0.28 to 0.97). The median overall survival was not reached. Important toxicities included anemia (28%), neutropenia (16%), pneumonia (16%), and venous thrombosis (5%). CONCLUSION: Generic pomalidomide-based therapy is an effective option and is well tolerated in patients with RRMM. Higher response rates and longer survival seen in our study are possibly because of heterogeneity of the study population.